0047 Circadian Regulation of Hunger is Similar in Lean and Non-lean Individuals. (12th April 2019) - Ordaz-Johnson, Omar; McHill, Andrew W; Thosar, Saurabh S; Bowles, Nicole P; Berman, Alec M; Herzig, Maya X; Roberts, Sally A; Clemons, Noal A; Morimoto, Miki; Butler, Matthew P; Emens, Jonathan S; Shea, Steven A
Abstract: Introduction: Hunger in young, lean individuals is modulated by a circadian rhythm which is lowest near 8AM and peaks around 8PM. Further, later circadian timing of food intake is independently associated with increased body fat. It is unknown, however, whether the circadian rhythm in hunger in non-lean (BMI>25 kg/m 2 ) individuals is delayed or disproportionately higher at a particular circadian phase as compared to lean (BMI≤25 kg/m 2 ) individuals, potentially providing a mechanism for increased food intake at later circadian times. We therefore investigated subjective hunger in lean and non-lean individuals under tightly controlled laboratory conditions. Methods: After 1-3 weeks of an 8h regular and habitual sleep schedule at home, 22 healthy participants (aged 52±7 years [mean±SD]; 11 female) underwent a 5-day in-laboratory circadian protocol free of time cues and in dim-lighting. The protocol consisted of ten recurring 5 h 20 min cycles in which all scheduled behaviors—including meals—were identical and evenly distributed across the circadian cycle. Meals were designed via Harris-Benedict equation to meet each participant's caloric needs. Lean (n=7; BMI: 23.1±2 kg/m 2 ; age: 52±9 years) and non-lean (n=15; BMI: 30.6±5.4 kg/m 2 ; age: 52±7 years) participants were identified. Hunger was measured regularly via visual analog scale and circadian phase was calculated relative to salivary dim-light melatonin onset (>3 pg/mL threshold). Data were analyzed using mixed-effect models and significance was set at p<0.05. Results: On average, subjective hunger scores followed a significant circadian pattern (p=0.003) independent of all scheduled behaviors; hunger trough/peak for this cohort was 4AM/ 9PM. The respective rhythms between lean and non-lean groups were not significantly different (p=0.19); furthermore, the interaction of group by circadian phase was not significant (p=0.45). Conclusion: The present findings suggest that increased evening intake in non-lean individuals is not due to a different rhythm in hunger. Future work should assess the contribution of other behavioral factors leading to the later circadian timing of intake in non-lean individuals. Support (If Any): Work reported in this poster was supported by the National Institutes of Health Common Fund and Office of Scientific Workforce Diversity (UL1GM118964, RL5GM118963, TL4GM118965).